TRADITIONAL REPETITION PATTERNS IN THE CREATIVE PROCESS OF THE KETUT SUGANTIKA LEKUNG’S POROSAN SERIES - Budiaprilliana, Luh (Institut Seni Indonesia Denpasar, 2024)
This research examines the repetition patterns found in the creative process of Ketut Sugantika Lekung's Porosan Series artworks. Porosan Series is one of Ketut Sugantika Lekung's artworks, inspired by the shape and the making process of a sacred ritual object called Porosan. In general, Porosan Series artworks display visualizations that emphasize the impression of repetition. The creative process of the Porosan Series imitates the process of making the original Porosan. Imitation activities in this creative process were studied to see the influence of traditional repetition patterns originating from making original porosan. This research uses a descriptive method with a qualitative approach, which emphasizes more in-depth data analysis. The results of the research show indications of the influence of original porosan making's traditional repetition pattern in the creative process of the Porosan Series. The Porosan Series creative process also uses three stages like the original porosan: preparation, realization, and finishing, but the original Porosan's final stage is drying, not finishing. Even though there are several modifications, the strong influence of the traditional repetition pattern is still visible because it shows some behaviors that are similar in every stage and process between the two things, such as focus, relaxation, and sincerity, thus creating a meditative state without realizing it. This research is essential to see the impact of local wisdom, which can positively influence the creative process of original Balinese artists to create a potential new method based on Balinese traditions and local wisdom.